The West in Early Cinema After the Beginning - Verhoeff, Nanna (Film Culture in Transition, 2006)
Verhoeff investigates the emergence of the western genre, made in the first two decades of cinema (1895-1915). By analyzing many unknown and forgotten films from international archives she traces the relationships between films about the American West, their surrounding films, and other popular media such as photography, painting, (pulp) literature, Wild West Shows and popular ethnography. Through this exploration of archival material she raises new questions of historiography and provides a model for historical analysis. These first traces of the Western film reveal a preoccupation with presence and actuality that informs us about the way in which film, as new medium, took shape within the context of its contemporary visual culture.